100 million unnecessary returns : a simple, fair, and competitive tax plan for the United States : with a new introduction - Graetz, Michael J. (Yale University Press, 2010)
"To most Americans, the United States tax code has become a vast and confounding puzzle. In 1940, the instructions to the form 1040 were about four pages long. Today they have ballooned to more than a hundred pages, and the form itself contains more than ten schedules and twenty worksheets. The complete tax code totals about 2.8 million words--about four times the length of War and Peace. In this intriguing book, Michael Graetz maintains that our tax code has become a tangle of loopholes, paperwork, and inconsistencies--a massive social program that fails tests of simplicity and fairness. More important, our tax system has failed to keep pace with the changing economy, creating burdens and wastes of resources that weigh our nation down. Graetz offers a solution. Imagine a world in which most Americans pay no income tax at all, and those who do enjoy a far simpler tax process--all this without decreasing government revenues or removing key incentives for employer-sponsored health care plans and pensions. As Graetz adeptly and clearly describes, this world is within our grasp"--